Livestock and farming systems in Southeast Nigeria - Francis, P.A. (PUDOC, 1988)
Presents the results of a survey of small ruminant owners in four southeastern states of Nigeria, viz, Bendel, Anambra, Imo and Cross River. Relates livestock management systems to their socioeconomic and ecological environment and inturn to management practices and to characteristic problems and hazards facing small ruminant producers in the areas surveyed. Suggests the implications of the process of agricultural intensification for smallholder livestock production systems in the zone.